Nutritional, anti-nutritional evaluation, and element analysis of Trichosanthes lobata Roxb. (Cucurbitaceae) through inductively coupled plasma-mass spectrometry technique - Aghil Soorya Aravindakshan; Sekar Thangavel (Wolters Kluwer Medknow Publications, 2021)
Background: The search for a drug from plant source starts with its investigations on primary and preliminary compositions that further lead the research in its right path. Objective: The objective is to investigate the organoleptic, proximate composition and to quantify the mineral, nutritional, and anti-nutritional values of Trichosanthes lobata Roxb. Materials and Methods: Organoleptic, macroscopic, microscopic, physicochemical, proximate, nutritional, anti-nutritional compositions of T. lobata leaves and stem were evaluated using standard methods. Further mineral composition of the species was analyzed using inductively coupled plasma-mass spectrometry technique. Results: The organoleptic, macroscopic, microscopic, physicochemical, and proximate analysis revealed the good quality, purity, and active principles in the T. lobata. All the evaluations concluded that the leaf of the species possess better compositions that the stem. The fair quantity of carbohydrate (27.32 mg GU eq./g), starch (32.44 mg GU eq./g), protein (52.49 mg bovine serum albumin eq./g), amino acid (33.77 mg LE eq./g), Vitamin C (12.68 mg ascorbic acid equivalent eq./g), and Vitamin E (8.21 mg α-TOP eq./g) were seen in leaves. Similarly, minerals such as magnesium, potassium, calcium, sodium, lithium, iron, zinc, aluminum, copper, nickel, and chromium were found in notable quantities in leaves. The anti nutritional analysis of trypsin inhibitors (0.013 TIU/mg), oxalate (0.002%), cyanogen (below detection level (BDL)), and phytic acid (BDL) indicates the low toxicity profile of the species. All the results satisfy the requirements and receive the toxicity boundaries set by the World Health Organization and EFSA. Conclusion: T. lobata leaves possess notable nutritional values.